Traditional Techniques for the Management of Cactaceae in the Americas: The Relationship between Use and Conservation - Pedrosa, Kamila Marques; Lucena, Camila Marques; Lucena, Reinaldo Farias Paiva; Lopes, Sérgio de Faria (Ethnobiology Letters, 2018)
Humans have used and coexisted with cacti in arid regions of North and South America for thousands of years. Species of the family Cactaceae possess physiological adaptations to arid and semi-arid climates that have allowed them to be used as a resource throughout the year by traditional peoples. The objective of this review is to present information on the uses and management of species of Cactaceae in the various regions of the Americas. This review provides information relevant to conservation policies regarding this important resource for local populations in semi-arid regions. To fully understand how management can influence cacti conservation, a knowledge gap regarding the traditional management of cacti needs to be addressed.